SPE Oil and Gas India Conference and Exhibition 2010
DOI: 10.2118/129158-ms
|View full text |Cite
|
Sign up to set email alerts
|

Geomechanics, ECD Management and RSS to Manage Drilling Challenges in a Mature Field

Abstract: The Serang Field, offshore East Kalimantan, Indonesia was discovered in 1973. Production started in 1993. Although it is a mature field with 120 wells, drilling still faces challenges in the form of severe lost circulation and stuck pipe events. Side tracks often need to be drilled and drilling budget overruns can be significant. The 2006 drilling campaign of 5 wells saw the loss of several BHAs and needed 4 sidetracks, due to stuck pipe events. In order to improve the drilling operation and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…11,12 Ignoring these parameters will affect the ECD prediction, lead to inaccurate evaluation of ECD, and cause well control problems during the drilling operations. 13,14 ■ PREDICTING ECD BY EMPLOYING ML TECHNIQUES ECD prediction from the drilling data is considered a novel approach in the petroleum industry due to the limitations of the ECD downhole measurements. AI is a technique that utilizes high computing capabilities for processing advanced algorithms to solve technical/problematic issues by simulating the human brain's thinking manner.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 Ignoring these parameters will affect the ECD prediction, lead to inaccurate evaluation of ECD, and cause well control problems during the drilling operations. 13,14 ■ PREDICTING ECD BY EMPLOYING ML TECHNIQUES ECD prediction from the drilling data is considered a novel approach in the petroleum industry due to the limitations of the ECD downhole measurements. AI is a technique that utilizes high computing capabilities for processing advanced algorithms to solve technical/problematic issues by simulating the human brain's thinking manner.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The developed mathematical correlations are limited to some applications, and they ignore a lot of other input parameters that have an impact on the ECD values. Such ignored parameters are well geometry, fluid rheological properties, rotation of the drill string, and downhole pressure and temperature conditions, which affect the mud density, cuttings dispersion, hole cleaning, and swab and surge of drill pipe movements in the hole. , Ignoring these parameters will affect the ECD prediction, lead to inaccurate evaluation of ECD, and cause well control problems during the drilling operations. , …”
Section: Introductionmentioning
confidence: 99%
“…Such ignored parameters as well geometry, fluid rheological properties, the rotation of the drill string, downhole pressure and temperature conditions that affect the mud density, cuttings dispersion, hole cleaning, and swab and surge of drillpipe movements in the hole 12,13 . Ignoring these parameters will affect the ECD prediction and lead to the inaccurate evaluation of ECD and causes well control problems during the drilling operations 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…The role of geomechanics in minimising excessive drilling costs has been acknowledged by many researchers. Several authors [1][2][3][4][5][6][7] reported the benefit of having a pre-drilling geomechanical model. Their respective drilling challenges have been addressed by means of, but not limited to, the construction of a robust stress profile, the estimation of the rock elastic and strength properties, drilling trajectory evaluation, drilling fluid properties optimization, and casing seat design.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the non-productive time (NPT) could be reduced to as low as 2% by implementing pre-drill geomechanical modelling and real-time drilling geomechanics surveillance. Caicedo et al [2] also reported that the stuck pipe incidents could be eliminated after introducing a geomechanical approach into their drilling campaign. Their statistic reflects evidence that NPT was primarily associated with series of mud loss and pack-offs; however, the root cause of these incidents was initially unidentified.…”
Section: Introductionmentioning
confidence: 99%